2021
DOI: 10.3390/jof7080621
|View full text |Cite
|
Sign up to set email alerts
|

Soil Redox Controls CO2, CH4 and N2O Efflux from White-Rot Fungi in Temperate Forest Ecosystems

Abstract: Microaerophilic white-rot fungi (WRF) are impacted by oxygen depletion because of fluctuating redox occurrence in southern temperate forest soils of Chile (1500–5000 mm year−1). How these conditions influence WRF survival has been scarcely examined. We explored the contributions of WRF to greenhouse gas (GHG) emissions of N2O and CH4 and soil organic C oxidation (CO2) in five sterilized and inoculated forest soils derived from various parent materials and climates. The soil was incubated for 20 days following … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 74 publications
(80 reference statements)
0
3
0
Order By: Relevance
“…This effect is closely related to soil functional selection, which includes nutritional and physical conditions that favor the establishment of specific microorganisms over others ( Mimmo et al, 2014 ). Based on soil organic matter (SOM) availability and N content, previous research has shown that endemic microbiota can cause significant CO 2 flux and reactive oxygen species (ROS) production ( Merino et al, 2021a ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This effect is closely related to soil functional selection, which includes nutritional and physical conditions that favor the establishment of specific microorganisms over others ( Mimmo et al, 2014 ). Based on soil organic matter (SOM) availability and N content, previous research has shown that endemic microbiota can cause significant CO 2 flux and reactive oxygen species (ROS) production ( Merino et al, 2021a ).…”
Section: Discussionmentioning
confidence: 99%
“…Although SOM decomposition stimulates GHG release ( Merino et al, 2020 , 2021a ), it is unclear whether biotic (exoenzymes) and abiotic (e.g., Fenton reaction) ROS production can be correlated with soil carbon emission, and whether this mechanism is transversal to the forest with similar structure on a not local scale. This hypothesis appears to be dependent on optimal pH values for biotic GHG production, which is dependent on enzymatic activity and abiotic pathways ( Merino et al, 2021a ). The optimal soil pH for methanogenesis, according to some reports, is between 4 and 7, but higher CO 2 emissions were recorded at circumneutral pH ( Dalal and Allen, 2008 ).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous reports have emphasized that changes in land use influence soil fertility and soil organic matter (SOM) even for redox controls [5,6]. Many others, e.g., Baldrian [5], state that SOM transformation depends on the soil microorganisms' activity, mainly fungi and bacteria.…”
Section: Introductionmentioning
confidence: 99%